Density and integral use evaluation of three leguminous trees in silvopastoral systems in the tropic of Guerrero, Mexico (POLIBOTÁNICA, 2019)
In the Tropic of Guerrero Mexico the distribution, the density and uses of trees Pithecellobium dulce Roxb Benth, Gliricidia sepium (Jacq) Steud, Haematoxilum brasiletto Karst were studied and its foliage was added to the diets of kids and productive response and apparent digestibility was measured. The livestock farmers have six complementary uses (firewood, poles, shade, medicinal, human consumption and artisanal). The species were identified in live fences and scattered in paddocks with densities of 4.87 trees per 100 linear meters and 1.79 trees ha-1; P. dulce was the largest size and identified from 250 to 1332 masl. The ashes (P